Responsabilidade civil do estado por erro judiciário: prisão cautelar seguida de sentença absolutória - Thé Filho, Fábio de Weimar (Universidade Federal Rural do Semi-Árido, 2018)
The article deals with state liability, with focus on cases of imprisonment followed by acquittal. It is divided in three stages, and bibliographical research and deductive method was used in all of them to carry out structuring on the theme. First, are made general considerations about State Liability, as also the evolution of the treatment of this theme in Brazilian Federal Constitutions. Then, the literature is analyzed, presenting contrary and favorable arguments about State Liability in these cases. After, several precedents of Brazilian Federal Court are analized. At the end, it is concluded that even though the judicial decisions mean States’ soberany, there’s the duty of indemnify in cases os imprisonment followed by acquittal.
Artigo Acadêmico
Keywords: Responsabilidade civil do Estado; Erro judicial; Prisão indevida; State liability; Miscarriage of justice; Imprisonment followed by acquittal; CIENCIAS SOCIAIS APLICADAS::DIREITO